ELETRODOS DE PASTA DE CARBONO VÍTREO MODIFICADOS COM NANOPARTÍCULAS DE OURO ESTABILIZADAS EM PORFIRANA: POTENCIAIS APLICAÇÕES PARA A DETECÇÃO DO AGENTE ANTITUMORAL 5-FLUOROURACIL - Lima, Dhésmon (2016)
In this work, glassy carbon paste electrodes (GCPE) were modified with porphyran- capped gold nanoparticles (GCPE/AuNps-PFR) and applied for the determination of an anticancer drug, 5-fluorouracil (5-FU), by using differential pulse voltammetry (DPV). The PFR polysaccharide was isolated from commercial Nori seaweed, and its characterization was carried out by FTIR and 13C-NMR as well as by determining its total sugar and sulfate contents, which resulted in 82.8% and 11.9%, respectively. These experiments confirmed the chemical identity and purity of the extracted polysaccharide, which was used as reducing and capping agent to the synthesis of gold nanoparticles (AuNps-PFR). The temperature and the concentrations of AuCl4- and PFR for the AuNps-PFR synthesis were optimized by a 23 full factorial design including a central point assayed in triplicate. The smallest particles were produced with 128.7 nm by employing a temperature of 70 °C and concentrations of 2.5 mmol L-1 for AuCl4- and 0.25 mg mL-1 for PFR. The characterization of the AuNps-PFR nanocomposite was performed by UV-VIS, FTIR and DLS spectroscopies, FESEM, zeta potential and XRD. The UV-VIS spectrum showed an absorption at 524 nm (plasmon band), with no significant changes in its shape and absorption frequency for 90 days. This observation suggests that the AuNps-PFR are stable in suspension, which is in good agreement with the zeta potential of -30.5 mV obtained for the sample. The FTIR spectrum revealed that interactions between the AuNps and the PFR may exist, as a consequence of displacements in the frequency of the bands in the AuNps-PFR spectrum compared to that obtained for the PFR individually. The electrochemical characterization of the porphyran modified GCPE (GCPE/PFR) was carried out by cyclic voltammetry and electrochemical impedance spectroscopy in the presence of the Fe(CN)63-/4- probe, revealing that the polysaccharide had a positive effect on the electrode response, since higher current values and a lower charge transfer resistance for the electrochemical probe redox process were achieved compared to the unmodified GCPE. Even better responses were obtained after the modification of the GCPE with the synthetized AuNps-PFR, as a consequence of the high electrical conductivity and large surface area displayed by the nanocomposite. The 5-FU was oxidized on the GCPE/AuNps-PFR surface according to an irreversible, pH dependent and diffusion controlled mechanism, showing an anodic wave at +1,1 V in BR buffer solution 0.04 mol L-1. The highest current value for 5-FU determination was achieved in BR buffer with pH 8.0, by DPV; therefore, this value was chosen for the further analysis. A linear relationship was observed between the anodic peak potential and the pH of the medium with a slope of -69 mV pH-1, demonstrating that the same number of protons an electrons participate in the 5-FU oxidation mechanism. The GCPE/AuNps-PFR exhibited a linear relationship between the peak current and 5-FU concentration over the range of 29.9 to 234.0 μmol L-1, with low detection (0.66 μmol L-1) and quantification limits (2.22 μmol L-1). Besides the good sensitivity for detecting 5-FU, the modified electrode showed reproducibility, and its response was not influenced by interfering compounds such as glucose, urea, albumin, ascorbic acid, Na+ and K+, suggesting its potential application to determine 5-FU in biologic matrices. The practical utility of the developed sensor was demonstrated for the quantification of 5-FU in pharmaceutical injection sample. A good average recovery percentage of 104.0% was achieved, with an acceptable relative standard deviation of 2.25%. So, these results could confirm the promising analytical performance of the modified electrode for the electroanalysis of 5-FU in real samples.